Community participatory approach of waste mitigation in the marine environment of Semporna - Prabhakaran, Sudesh; Nair, Vikneswaran; Ramachandran, Sridar (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Semporna, a district in the east cost of Sabah is popular due to its marine tourism activities. The ethnic groups found are mainly the Bajau, Suluk, Bugis and Palauan, also known as the sea gypsies. Waste disposal in the marine environment in this district is a serious problem. The locals mainly live in stilt houses which do not have proper sewage nor rubbish collection system.